Aspectos da atividade farmacêutica e caracterização da prescrição médica em oncologia - Lena, Angela Regasson (2024)
The analysis of medical prescriptions is one of the most important activities in the pharmacists field, as it prevents errors, promotes rational drug use, and reduces patient hospitalization time. An error in a medical prescription not only fails to achieve the expected therapeutic result but can also result in patient harm. The aim of this study was to describe pharmacists' experiences regarding the analysis of medical prescriptions and to analyze the prescriptions of patients undergoing outpatient oncology treatment, identifying prescription errors. This exploratory, observational, cross-sectional, retrospective, and qualitative-quantitative study was conducted in two phases. In the first phase, seven pharmacists from different oncology services in the southern part of the country were interviewed, most of whom were female and aged between 30 and 40 years. All were oncology specialists, with most having between 5 and 10 years of experience in the field. Most services used electronic prescriptions, and when asked about the main difficulties encountered in pharmaceutical prescription analysis, pharmacists reported issues such as incomplete data on the prescription and/or lack of patient information. The absence of this information in medical prescriptions can lead to doubts and errors, reduce the efficacy and quality of care provided, and pose risks to the patient. In the second phase, the medical prescriptions of patients receiving outpatient oncology treatment at one of the oncology services in the southern part of the country were analyzed to identify prescription errors. A total of 255 prescriptions containing 581 prescribed medications were analyzed. The average number of errors was 4.34 per prescription, related to the volume and type of diluent; infusion time; and medication dose. By describing the pharmaceutical analysis conducted and the prevalence of the most common errors, improvements can be proposed to enhance patient care, contributing to the safe and rational use of medications. The results also indicated that the medical prescription system used by the studied service could be improved by ensuring that all information about the medications is completed.